Publisher Correction: Synergistic electroreduction of carbon dioxide to carbon monoxide on bimetallic layered conjugated metal-organic frameworks - Haixia Zhong (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.